UJI AKTIVITAS ANTIOKSIDAN FRAKSI N-HEKSANA KULIT BUAH NAGA MERAH (Hylocereus lemairei Britton dan Rose) MENGGUNAKAN METODE DPPH (1,1-DIFENIL-2-PIKRILHIDRAZIL) - ., Widyo Budilaksono (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
WHOs (World Health Organization) data in 2011 showed that somedegenerative diseases included as the top ten causes of death in the world. One of themain trigger of degenerative diseases is free radical. The importance substrate that canreduce negative impact of free radicals attack is antioxidant. Red dragon fruit(Hylocerueus lemairei Britton and Rose) has a potential to develope as the source ofnatural antioxidant. This study aims to determine the antioxidant activity of n-hexanefraction of red dragon fruit peel. Red dragon fruit peel powder macerated withinchloroform, and macerate then fractionated with n-hexane. The result of phytochemicalscreening showed that the n-hexane fraction contains flavonoid, alkaloid and steroid.Preliminary test conducted on sample by using Thin Layer Chromatography (TLC) with amixture mobile phase of n-hexane and ethyl acatate (10:1). The result indicated thepresence of whitish yellow spots on a purple background at silica gel 60 Fwhensprayed 0,2 % DPPH solution, with Rf values at 0,22; 0,29; 0,36; 0,52; 0,67 and 0,88.Antioxidant activity assay of n-hexane fraction of red dragon fruit peel performed byusing the DPPH (1,1-difenil-2-pikrilhidrazil) method with UV-Vis spectrophotometricmeasurements at ?max515,50 nm, and its showed that sample had ICat 206,591 ?g/mLand considered as less active antioxidant, whereas vitamin C had much lower IC50value(2,973 ?g/mL) and considered as very powerfull antioxidant. Keywords : Antioxidant, N-Hexane Fraction, Red Dragon Fruit Peel, TLC, DPPH